2015
DOI: 10.3233/ch-151998
|View full text |Cite
|
Sign up to set email alerts
|

Shell matters: Magnetic targeting of SPIONs and in vitro effects on endothelial and monocytic cell function

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are versatile and easily functionalized agents with high potential for diagnostic and therapeutic intravascular applications. In this study, we analyzed the responses of endothelial (ECs) and monocytic cells to three different types of SPIONs, in order to assess the influence of physico-chemical properties on the biological reactions to SPIONs. The following formulations were used: (1) Lauric acid-coated and BSA-stabilized SPION-1,(2) Lauric acid/BSA-coated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The considerable differences in the physicochemical properties of SPIONs resulted in dramatic differences of their magnetic accumulation under flow conditions, as also shown in our previous in vitro studies 16 . Out of the three types of SPIONs tested in the ex vivo artery model, SPION-1 had by far the largest capacity to accumulate at the artery segment placed directly under the tip of the magnet, corresponding to the magnetic field gradient of about 40 T/m at the artery centre ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The considerable differences in the physicochemical properties of SPIONs resulted in dramatic differences of their magnetic accumulation under flow conditions, as also shown in our previous in vitro studies 16 . Out of the three types of SPIONs tested in the ex vivo artery model, SPION-1 had by far the largest capacity to accumulate at the artery segment placed directly under the tip of the magnet, corresponding to the magnetic field gradient of about 40 T/m at the artery centre ( Fig.…”
Section: Resultssupporting
confidence: 81%
“… 20 . In support of their hypothesis, a successful accumulation of circulating SPIONs under external magnets has been demonstrated in several in vitro models of straight 21 22 and bifurcating channels 16 23 24 . Furthermore, our previous experimental ex vivo work in bovine arteries 14 25 showed that accumulation of flowing SPIONs in the arterial wall is achievable under the guidance of a sufficiently strong external magnet, as confirmed by histology, microCT and magnetorelaxometry 14 26 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…27 Compared to the previously marketed dextran-coated contrast agent ferumoxides, SPIONdex have several distinct and improved characteristics. Ferumoxides was composed of magnetite nanoparticles with iron concentration 11.2 mg/mL, hydrodynamic diameter 120-150 nm, and zeta potential -13 mV.…”
Section: Introductionmentioning
confidence: 99%
“…46 In our in vitro experiments, the probability of a partial sedimentation during cell culture experiments is higher with SPION LA followed by SPION LA-HSA and SPION Dex , which possibly results in higher SPION LA uptake and toxicity. To what extent sedimentation of these SPIONs influences dose-response curves 47 and how the uptake and toxicity can affect the in vivo administration are difficult to foresee. Models and methodologies for particle dosimetry that enables the determination of the dosage delivered to cells have already been presented, and it has been shown that usage of the cellular dose rather than administered dose improves the correlation between dose and response to particles in vitro and in vivo.…”
mentioning
confidence: 99%